"Someone to Have My Back": Exploring the Needs of Racially and Ethnically Diverse Lesbian, Gay, Bisexual, and Transgender High School Students. Issue 4 (22nd August 2018) - Craig, Shelley L; McInroy, Lauren B; Austin, Ashley
Abstract: A school-based needs assessment was undertaken with a sample of primarily Hispanic and African American lesbian, gay, bisexual, and transgender (LGBT) ( N = 180) high school students in the United States. Applying grounded theory techniques, researchers conducted focus groups using a semistructured protocol that included a vision question. Five themes illuminating physical and emotional safety needs emerged after the analysis: (1) a safe place to stay, (2) safe schools and communities, (3) more than just pockets of safety, (4) someone to have my back, and (5) someone for my family. Strategies are suggested for school social workers, school counselors, and other school-based counseling professionals to address the needs of LGBT students.